TRADITIONAL UZBEK WOMEN’S CLOTHING: THE TECHNOLOGIES AND TECHNIQUES OF ATLAS AND ADRAS FABRICS - Ochilova Marjona O‘tkir qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article examines the techniques and technologies used in the creation of traditional Uzbek women’s clothing, focusing on atlas and adras fabrics. The study explores methods of embroidery, weaving, pattern design, and tailoring, highlighting their role in preserving cultural heritage and aesthetic values. The integration of modern technologies and innovations in garment production is also discussed.